Evaluation of knowledge levels amongst village AIDS committees after undergoing HIV educational sessions: results from a pilot study in rural Tanzania - Epsley Elizabeth J; Nhandi Benjamin; Wringe Alison; Urassa Mark; Todd Jim (BMC, 2011)
Abstract Background Village AIDS committees (VAC) were formed by the Tanzanian government in 2003 to provide HIV education to their communities. However, their potential has not been realised due to their limited knowledge and misconceptions surrounding HIV, which could be addressed through training of VAC members. In an attempt to increase HIV knowledge levels and address common misconceptions amongst the VACs, an HIV curriculum was delivered to members in rural north western Tanzania. Methods An evaluation of HIV knowledge was conducted prior to and post-delivery of HIV training sessions, within members of three VACs in Kisesa ward. Quantitative surveys were used with several open-ended questions to identify local misconceptions and evaluate HIV knowledge levels. Short educational training sessions covering HIV transmission, prevention and treatment were conducted, with each VAC using quizzes, role-plays and participatory learning and action tools. Post-training surveys occurred up to seven days after the final training session. Results Before the training, "good" HIV knowledge was higher amongst men than women (p = 0.041), and among those with previous HIV education (p = 0.002). The trade-centre had a faster turn-over of VAC members, and proximity to the trade-centre was associated with a shorter time on the committee. Training improved HIV knowledge levels with more members achieving a "good" score in the post-training survey compared with the baseline survey (p = < 0.001). The training programme was popular, with 100% of participants requesting further HIV training in the future and 51.7% requesting training at three-monthly intervals. Conclusions In this setting, a series of HIV training sessions for VACs demonstrated encouraging results, with increased HIV knowledge levels following short educational sessions. Further work is required to assess the success of VAC members in disseminating this HIV education to their communities, as well as up-scaling this pilot study to other regions in Tanzania with different misconceptions.